Factors Affecting Economic Development and Job Opportunity in Samarinda - Aji Alya Ananda (Indonesian Journal of Multidisciplinary Science, 2022)
This study aims to determine the Effect of Household Consumption and Investment on Economic Growth and Employment Opportunities in Samarinda City. Quantitative type of research. With a total of 15 years of research period calculated from 2006 - 2020.  The analytical tools used are  outer model, inner model, partial hypothesis testing with SmartPLS. The results showed that household consumption variables with food and non-food sector consumption indicators have a significant effect on economic growth. Investment variables with indicators of Domestic Investment (PMDN) and Foreign Investment (FDI) have a significant effect on economic growth. Variable Household consumption with indicators of consumption in the food and non-food sectors has a significant effect on employment opportunities. Meanwhile, investment variables with indicators of Domestic Investment (PMDN) and Foreign Investment (FDI) do not affect employment opportunities. The variable economic growth with the prevailing price GRDP indicator and constant price GRDP has a significant effect on job opportunities in Samarinda City for the period 2006 - 2020.